Meja Kopi Moden Pelbagai Fungsi Diinspirasikan oleh Palmanova, Itali - Husuno, Nadzirah; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2020)
The coffee table is used for convenient support of beverages, goods, decorative objects, and other small items as well as acts as decorative furniture for the living room. To date, the coffee tables produced by Fair Production Sdn. Bhd. has a poor design (bulky, sharp edges, and outdated) and functions as a coffee table only, which not fulfill today’s customers’ needs. Therefore, this study aims to design and develop a modern and multifunctional coffee table inspired by Palmanova, Italy for a small size living room. Various steps including a survey on the existing issues and design criteria needed in designing a new coffee table, creating sketches, and developing a miniature as well as the prototype. The survey shows that respondents were keener to possess a rectangular-shape coffee table with drawers as a compartment. Moreover, the coffee table made from combination materials viz. wood and metal with white color as a finishing touch become the preferences of the majority of the respondents. A modern and multifunction coffee table prototype was developed as a design suggestion for Fair Production Sdn. Bhd. in order to increase and expand their coffee table sales by providing current and meet the design criteria voted by respondents via survey.